TAXONOMIC REVISION OF ASIAN GENUS GLYPTOPETALUM THWAITES (CELASTRACEAE R. BR.) - Ivan A. Savinov (BRIN Publishing (Penerbit BRIN), 2014)
Taxonomic survey of Asian genus Glyptopetalum Thwaites (Celastraceae R. Br.) is presented. Thirty five species taxa of Glyptopetalum are accepted, including one new species, G. vidalii I. Savinov (Laos, Thailand), a new record for China, G. tonkinense Pitard (SE Yunnan) and a new record for Cambodia, G. quadrangulare Prain ex King, a new record for Indonesia - G. euonymoides Merr. and a new record for Philippines, Mindanao island - G. loheri Merr.